THE ROLE OF THE SHARIA CAPITAL MARKET IN ENCOURAGING ECONOMIC GROWTH IN INDONESIA - M. Guffar Harahap; Namira Anjani (CV. Barokah Publsiher, 2026)
The capital market is one of the investment instruments that is increasingly in demand by the public as the needs of modern financial management increase. The development of the capital market in Indonesia does not only occur in conventional instruments, but also in sharia instruments that have characteristics according to Islamic principles. This research aims to examine the benefits of the Islamic capital market as an investment instrument and its contribution to national economic growth. The research uses a normative method with descriptive analysis based on DSN-MUI literature, regulations, and fatwas. The results of the study show that the existence of the Islamic capital market not only provides halal investment alternatives, but also plays a role in reducing speculative practices, increasing transparency, and strengthening economic stability. The affirmation of regulations and the improvement of sharia instruments have been proven to encourage the growth of investors and issuers in the sharia capital market. Thus, the sharia capital market has a significant contribution in expanding public participation, supporting the development of the real sector, and encouraging Indonesia's economic growth.